1998
DOI: 10.1046/j.1365-2249.1998.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes are not the target for estradiol-mediated suppression of DTH in reconstituted female severe combined immunodeficient (SCID) mice

Abstract: Oestrogen has the capacity to suppress T cell-dependent DTH. To explore the mechanisms whereby oestrogen exerts its effects on the immune system we have used SCID mice which are largely devoid of functional T and B lymphocytes, hence being unable to raise DTH, but display intact antigen-presenting capacity. Transfer of lymphocytes to SCID mice restores the DTH capacity. In order to analyse if oestrogen down-regulates DTH by a direct action on T cells we reconstituted SCID mice with either splenocytes or thymoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…We found that, at 4 weeks, spleen T cells were 2.0 Ϯ 0.2% in control nude mice and 8.6 Ϯ 0.3% in T cell-reconstituted mice (P Ͻ 0.05). Similar numbers of spleen T cells have been found by others after T cell reconstitution (14,15). Thus, the data establish that our procedure was effective in reconstituting T cells in nude mice.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…We found that, at 4 weeks, spleen T cells were 2.0 Ϯ 0.2% in control nude mice and 8.6 Ϯ 0.3% in T cell-reconstituted mice (P Ͻ 0.05). Similar numbers of spleen T cells have been found by others after T cell reconstitution (14,15). Thus, the data establish that our procedure was effective in reconstituting T cells in nude mice.…”
Section: Methodssupporting
confidence: 89%
“…T cells (1 ϫ 10 7 ) then were injected i.v. into the lateral tail vein of allotype-congenic C57BL͞6 nude recipients by using established methods (14,15). On the same day, T cell-reconstituted mice were subjected to either ovx or sham operation.…”
Section: Methodsmentioning
confidence: 99%
“…Innate immunity and macrophages have, therefore, been suggested to play a role (17). Estrogen has been reported to suppress T cell-dependent DTH and activation of inflammatory cells producing TNF-␣ and IFN-␥ (51)(52)(53)58). Our data suggest a downregulation of the Th1 response associated to DNB colitis as reflected by decreased IFN-␥ mRNA expression 14 days postcolitis in 17␤-estradiol-treated mice.…”
Section: Discussionmentioning
confidence: 53%
“…The existence of such a regulatory mechanism has been described in models of T cell-mediated delayedtype hypersensitivity, where estrogen has been found to suppress T-cell proliferation through targeting of antigen-presenting cells (51,52). Similarly, previous reports from our laboratory demonstrated that estrogen represses stromal cell-soluble M-CSF production through targeting of IL-1-and TNF-producing bone marrow cells, rather than through a direct effect on mature stromal cells (16,27).…”
Section: Sham Ovx Ovx Estrogen T Cells T Cells T Cellsmentioning
confidence: 59%